1994
DOI: 10.1111/j.1399-6576.1994.tb03915.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of continuous epidural infusion of morphine/bupivacaine with fentanyl/ bupivacaine for postoperative pain relief

Abstract: The efficacy and safety of postoperative analgesia with continuous epidural infusion of either morphine or fentanyl in combination with bupivacaine were evaluated in 85 patients, ASA physical status I or II, undergoing thoracic and/or upper abdominal surgery. Patients were treated with one of the combinations for 48 h after surgery. The morphine/bupivacaine group (MB; n = 45) received morphine at the rate of 0.2 mg.h-1, and bupivacaine at the rate of 10 mg.h-1 for the first 24 h or 5 mg.h-1 for the second 24 h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
0

Year Published

1995
1995
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 17 publications
2
18
0
Order By: Relevance
“…In the study by Claude Mann et al 20 pain relief was better at rest and after coughing in the PCEA group and the satisfaction scores were significantly greater in the PCEA group. In the study conducted by Saito et al, 21 the efficacy and safety of postoperative analgesia with continuous epidural infusion of either morphine or fentanyl in combination with bupivacaine were evaluated.…”
Section: Discussionmentioning
confidence: 99%
“…In the study by Claude Mann et al 20 pain relief was better at rest and after coughing in the PCEA group and the satisfaction scores were significantly greater in the PCEA group. In the study conducted by Saito et al, 21 the efficacy and safety of postoperative analgesia with continuous epidural infusion of either morphine or fentanyl in combination with bupivacaine were evaluated.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have confirmed our results showing similar analgesia with continuous epidural BM and BF. [6][7][8] Other than nausea as a marker for return of bowel function, no study has compared the effects of continuous epidural fentanyl and morphine on postoperative gastrointestinal recovery. Fischer et al concluded that continuous epidural BF resulted in less nausea than BM but this study lasted only 24 hr.…”
Section: Discussionmentioning
confidence: 99%
“…Problems associated with thoracic epidural blocks include the increased risk of sympathectomy producing orthostatic hypotension. 1,7 In our institution we have successfully used a lumbar approach for the past ten years for postoperative analgesia following major pelvic surgery thus minimizing the potentially deleterious effects on blood pressure.…”
Section: Discussionmentioning
confidence: 99%
“…However, evidence of the usefulness of epidural analgesia in the recovery of gut motility is based on clinical observations such as reduced time intervals before the first flatus and the first bowel movement, reduced time elapse before the first oral intake, and a reduction in the frequency of nausea and abdominal symptoms (Saito, 1994;Carli et al, 2001). These widely used clinical determinants of the resumption of gastrointestinal motility are very subjective.…”
Section: Epidural Analgesia and Gastrointestinal Motilitymentioning
confidence: 99%
“…Recent studies of the relationship between epidural analgesia and gastrointestinal motility have indicated the need for further investigation in this field (Shibata et al, 1994;Park et al, 2001;Moraca et al, 2003;Delaney et al, 2004). Clinical studies on post-surgical gastrointestinal motility have used indicators such as the occurrence of the first flatus, the time required to resume oral intake, or the recovery of bowel sounds (Saito et al, 1994;Carli et al, 2001). However, the significance of these indices as a parameter of gastrointestinal function remains controversial.…”
Section: Introductionmentioning
confidence: 99%